PERAN UKURAN PERUSAHAAN, UKURAN KANTOR AKUNTAN PUBLIK, DAN OPINI AUDIT DALAM AUDIT DELAY (Media Riset Akuntansi, 2022)
This study aims to analyze the effect of Firm Size, Public Accounting Firm Size, Audit Opinion on Audit Delays in Property, Real Estate and Building Construction sector companies listed on the Indoensia Stock Exchange in 2016-2020. The sampling method in this research is purposive sampling. The data analysis technique used is descriptive statistical analysis and multiple linear analysis. Data analysis process that carried out fisrt is descriptive statistic, classical assumption tests, multiple linear analysis and then hypothesis testing using SPSS version 25 software. The result show that the public accounting firm size had a possitive effect on audit delay, while firm size and audit opinion had negative effect on audit delay.